Moving Toward the Future of Policing - Treverton, Gregory F. (RAND Corporation, 2011)
Advances in technology and operating concepts are driving significant changes in the day-to-day operations of future police forces. This book explores potential visions of the future of policing, based on the drivers of jurisdiction, technology, and threat, and includes concrete steps for implementation. The analysis is based on a review of policing methods and theories from the 19th century to the present day.